Pathways to poor educational outcomes for HIV/AIDS-affected youth in South Africa - Orkin, M.; Boyes, Mark; Cluver, L.; Zhang, Y. (Routledge, 2014)
A recent systematic review of studies in the developing world has critically examined linkages from familial HIV/AIDS and associated factors such as poverty and child mental health to negative child educational outcomes. In line with several recommendations in the review, the current study modelled relationships between familial HIV/AIDS, poverty, child internalising problems, gender and four educational outcomes: non-enrolment at school, non-attendance, deficits in grade progression and concentration problems. Path analyses reveal no direct associations between familial HIV/AIDS and any of the educational outcomes. Instead, HIV/AIDS-orphanhood or caregiver HIV/AIDS-sickness impacted indirectly on educational outcomes via the poverty and internalising problems that they occasioned. This has implications for evidence-based policy inferences. For instance, by addressing such intervening variables generally, rather than by seeking to target families affected by HIV/AIDS, interventions could avoid exacerbating stigmatisation, while having a more direct and stronger impact on children's educational outcomes. This analytic approach also suggests that future research should seek to identify causal paths, and may include other intervening variables related to poverty (such as child housework and caring responsibilities) or to child mental health (such as stigma and abuse), that are linked to both familial HIV/AIDS and educational outcomes.